2007
DOI: 10.1007/s10038-007-0224-4
|View full text |Cite
|
Sign up to set email alerts
|

Austronesian genetic signature in East African Madagascar and Polynesia

Abstract: The dispersal of the Austronesian language family from Southeast Asia represents the last major diaspora leading to the peopling of Oceania to the East and the Indian Ocean to the West. Several theories have been proposed to explain the current locations, and the linguistic and cultural diversity of Austronesian populations. However, the existing data do not support unequivocally any given migrational scenario. In the current study, the genetic profile of 15 autosomal STR loci is reported for the first time fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…The admixture results reflect strong Melanesian influence in Fiji. Thus, using O1a as a marker for the later stages of the Austronesian expansion into Polynesia, given the paucity and the low frequencies at which it is found throughout the Pacific, is inappropriate and would provide fallacious support for the notion that Polynesian populations contain little or no genetic influences from Taiwan, which would contradict previously demonstrated genetic connections between these groups (Hagelberg et al, 1999;Kayser et al, 2003Kayser et al, , 2006Kayser et al, , 2008Lum, 1998;Melton et al, 1995;Regueiro et al, 2008). It is possible that the relative absence of haplogroup O1a in Polynesia and the Pacific may have been the result of the haplogroup being lost during the repeated bottleneck events experienced by the Austronesian migrants.…”
Section: Haplogroup O1a (M119): Unclear Connection To the Austronesiamentioning
confidence: 85%
See 1 more Smart Citation
“…The admixture results reflect strong Melanesian influence in Fiji. Thus, using O1a as a marker for the later stages of the Austronesian expansion into Polynesia, given the paucity and the low frequencies at which it is found throughout the Pacific, is inappropriate and would provide fallacious support for the notion that Polynesian populations contain little or no genetic influences from Taiwan, which would contradict previously demonstrated genetic connections between these groups (Hagelberg et al, 1999;Kayser et al, 2003Kayser et al, , 2006Kayser et al, , 2008Lum, 1998;Melton et al, 1995;Regueiro et al, 2008). It is possible that the relative absence of haplogroup O1a in Polynesia and the Pacific may have been the result of the haplogroup being lost during the repeated bottleneck events experienced by the Austronesian migrants.…”
Section: Haplogroup O1a (M119): Unclear Connection To the Austronesiamentioning
confidence: 85%
“…Examination of 15 hypervariable autosomal STR loci by Regueiro et al (2008) indicated that approximately 76% and 24% of the Samoan and 65% and 35% of the Tongan autosomal gene pools are of Southeast Asian and Melanesian descent, respectively. These proportions are similar to those determined by Kayser et al (2008) using a set of 327 autosomal STR markers, who found that East Asians and Melanesians contributed 79% and 21%, respectively, to Polynesian groups.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,4 Clear genetic evidence for the SEA influence has been found on neighbouring Madagascar. [5][6][7][8] On the basis of Y chromosome and mitochondrial variation, ethnic groups with the strongest SEA biocultural features in Madagascar were estimated to have approximately 50% SEA ancestry. 5,8 In contrast to Madagascar where the language, Malagasy, is an Austronesian language with origins in SEA, the languages spoken on the Comoros are of Bantu origin.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, 90% of Malagasy vocabulary belongs to the Barito (6) or other subgroups of Austronesian languages of Island Southeast Asia (7)(8)(9). Although being less specific, genetic studies have generally confirmed the dual ancestry of the Malagasy population (10)(11)(12)(13)(14).…”
mentioning
confidence: 98%